Mental health, sleep quality, and hormonal circadian rhythms in pregnant women with threatened preterm labor: a prospective observational study - Xiao-Juan Wang; Xiao-Ting Li; Na Chen; Long Huang; Shui-Xiu Huang; Ting-Ting Chen; Gui-Hua Liu; Rong-Fang Hu (BMC, 2023)
Abstract Background Threatened preterm labor (TPL) is an important obstetrical challenge. Pregnant women with TPL may develop psychological and physical problems such as mental health disorders, sleep disturbance, and hormonal circadian rhythm disruption. This study aimed to investigate the current state of mental health, sleep quality, and circadian rhythms of cortisol and melatonin secretion in pregnant women with TPL and normal pregnant women (NPW). Methods A prospective observational clinical study was conducted at a maternal and child health hospital in Fuzhou, China, between June and July 2022. A total of 50 women between 32 and 36 weeks of gestation (TPL group, n = 20; NPW group, n = 30) were recruited. Data on anxiety symptom (Zung's Self-rating Anxiety Scale, SAS), depression symptom (Edinburgh Postnatal Depression Scale, EPDS), subjective sleep quality (Pittsburgh Sleep Quality Index, PSQI) and objective sleep outcomes (measured by actigraphy) of the pregnant women were collected at the time of enrolment. Salivary samples were collected once every 6 h (i.e., at 06:00, 12:00, 18:00, and 00:00) during 2 consecutive days to measure the circadian rhythm of hormone (cortisol and melatonin). Results There were no differences found in the total scores of SAS, EPDS scores, subjective sleep quality between the TPL and NPW groups (P > 0.05). In contrast, significant differences were found in sleep efficiency, total sleep time, wake time after sleep onset, and average awakening time between the groups (P < 0.05). The circadian rhythm of melatonin secretion was disrupted in the TPL group (P = 0.350); however, it was maintained in the NPW group (P = 0.044). The circadian rhythm of cortisol secretion was disrupted in both groups (P > 0.05). Conclusions In the third trimester of pregnancy, women with TPL suffer from poorer sleep quality and disruption of circadian rhythm of melatonin secretion compared with NPW. Nevertheless, there were no differences found in mental health (i.e., anxiety and depression) and circadian rhythm of cortisol secretion. Large-scale studies should be conducted to evaluate these changes in women with TPL. Trial registration The study was registered from Chinese Clinical Trial Registry (Number: ChiCTR2200060674) on 07/06/2022.